Impact of Road Clearings on the Movements of Three Understory Insectivorous Bird Species in the Brazilian Atlantic Forest - Ramos de Oliveira, Paulo Roberto [UNESP]; Alberts, Carlos Camargo [UNESP]; Francisco, Mercival Roberto (Wiley-Blackwell, 2011)
Recent studies on the impacts of forest fragmentation on understory insectivorous birds in the Neotropics have highlighted that even narrow linear clearings, such as roads, can affect the movements of this guild of birds. We used playback trials of territorial vocalizations to assess the movements of three understory insectivorous bird species across two unpaved roads bisecting Parque Estadual Carlos Botelho in southeast Brazil, located within one of the largest remaining continuous Atlantic Forests. Movement patterns varied among species. While Chamaeza campanisona never crossed these roads, Pyriglena leucoptera crossed them in almost 100 percent of tests. Although Conopophaga lineata exhibited a significantly lower number of crossings along cleared sites, it was eventually willing to traverse the roads, showing an intermediate pattern. Shaded areas with connected canopy did not improve birds' willingness to cross roads compared with areas where treecrowns were at least 3 m apart. Similarly, birds' willingness to cross an 8-m wide road with limited traffic (six vehicles/wk) was not significantly greater than that of a 12-m wide road with more intense traffic (41 vehicles/d). Our findings suggest that the negative impact of roads on bird movement is an issue that should be addressed by managers of Atlantic Forest conservation units, especially as economic development results in pressure to pave and widen roads.
Keywords: antbirds; Atlantic rain forest; linear clearings; Neotropics; road effects